Unveiling the nexus: Women’s empowerment, climate change and household well-being in Uzbekistan - Alvi, Muzna (International Food Policy Research Institute, 2024)
Presentation given November 14, 2024 for Nexus Gains Workshop on Aral Sea Basin conducted in Tashkent, Uzbekistan.